Energy loss researches of diamond microgrinded laser mirrors by Fourier optics methods - Staschuk, V.S.; Kononchuk, G.L.; Poperenko, L.V.; Stukalenko, V.V.; Filipov, Y.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The diffraction losses of laser mirrors were determined by using specially designed spectrometer of spatial frequencies. Reflection surface (70 mm diameter) was made by diamond microgrinding, but instead of an ideal plane, the circular phase grating was formed. The Fourier-optics was applied to measure a real shape of flat laser metal mirrors. We analysed the diffraction pattern of light reflected from metal mirror in the Fraunhofer zone and determined periodic deviation of a surface from an ideal plane and its parameter – spatial frequency.